Late-Onset OCD as a Potential Harbinger of Dementia With Lewy Bodies: A Report of Two Cases - Frileux, Solène; Millet, Bruno; Fossati, Philippe (Frontiers in Psychiatry, 2020)
Objectives: Obsessive-compulsive disorder usually begins in adolescence or young adulthood. OCD cases appearing after the age of 50 are rare, most often associated with inflammatory, brain lesions or neurodegenerative comorbidities. We describe two cases of late-onset Obsessive Compulsive Disorder followed by the development of Lewy body dementia and review the links between these two disorders. Methods and results: We describe the clinical history of two patients that first showed OCD symptoms at an atypical age (> 60 years). After several failed treatment attempts, they were hospitalized in our unit. Both presented severe sensitivity to antipsychotic agents, that led to a diagnosis of Lewy Body Dementia. Administration of cholinesterase inhibitors was associated with decrease of psychiatric symptoms in both cases. In addition to those clinical observations, a systematic review of the literature suggests that, in addition to the prefrontal cortex, temporal lobe and putamen have important roles in OCD pathophysiology. Based on these findings, we discuss four hypotheses to explain the sequential appearance of OCD and LBD symptoms. First, we considered the possibility that comorbidity of OCD with LBD was coincidental. Second, we propose to interpret OCD symptoms as motor stereotypies. Third, we hypothesize that late-onset OCD might be a symptom of late-onset depression. Four, we hypothesize that through early deterioration of basal ganglia, LBD caused the onset of OCD. Conclusion: In conclusion, we recommend that cases of late-onset treatment-resistant OCD should be carefully tested for possible organic aetiologies, and for LBD dementia in particular.